(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
The aim of this study was to document the taxonomical, morphological, anatomical, palynological and cytological characters, and geographical distribution of endemic Aubrieta pinardii Boiss. (Brassicaceae) from Turkey. The description of the taxon was revised as a consequence of comprehensive assessments of many specimens. The surface pictures belonging to seed and pollen of the taxon were obtained by Scanning Electron Microscope. The seed surface ornamentation was rugose. The pollen was radially and isopolar and prolate in forms, with polar axes of 19.52 ± 0.29 μm and equatorial axes of 13.04 ± 0.22 μm, with oval outlines in the equatorial axes, and elliptical in the polar axes. They were three–colpate and colpus sizes varied between 12.98 μm and 13.29 μm in length, and between 1.33 and 2.09 μm in width. Also, the anatomical structures of the root, stem and leaf of species were studied. In cytological studies, the chromosome number of species was found as 2n = 16 (x =8). This was the first work including taxonomical, morphological (macro and micro), anatomical and cytological data of endemic Aubrieta pinardii. Bangladesh J.Plant Taxon. 27(1): 27-35, 2020 (June)